1996
DOI: 10.1002/(sici)1097-0215(19960917)67:6<800::aid-ijc8>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Heat-shock protein expression in cisplatin-sensitive and -resistant human tumor cells

Abstract: It has been suggested that the expression of certain heatshock proteins (HSPs) may be prognostic markers in several tumor types. Since HSPs may be involved in determining cellular sensitivity to chemotherapeutic drugs, the possible relation between HSP expression and cisplatin (cDDP) sensitivity was studied. Three human germ-cell tumor cell lines, I human small-cell lung carcinoma (SCLC) cell line and 3 human colon carcinoma cell lines were used as a model for differences in intrinsic cDDP sensitivity. The con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 27 publications
(10 reference statements)
1
23
0
2
Order By: Relevance
“…This effect was found regardless of the thermal dose applied, indicating that the degree of inducible HSPs, which are higher after a more severe thermal stress, is not critical in conferring or impacting resistance. This observation is consistent with previous evidence that tumor cells with more HSPs are not more resistant to chemotherapy than those with low basal levels [30]. Most importantly, it disproves the hypothesis that pre-treatment of cells with heat shock results in an increased resistance to proteasome inhibitors [27,31].…”
Section: Discussionsupporting
confidence: 90%
“…This effect was found regardless of the thermal dose applied, indicating that the degree of inducible HSPs, which are higher after a more severe thermal stress, is not critical in conferring or impacting resistance. This observation is consistent with previous evidence that tumor cells with more HSPs are not more resistant to chemotherapy than those with low basal levels [30]. Most importantly, it disproves the hypothesis that pre-treatment of cells with heat shock results in an increased resistance to proteasome inhibitors [27,31].…”
Section: Discussionsupporting
confidence: 90%
“…Acquired resistance to the chemotherapeutic drug cisplatin was also found to be accompanied by a decreased HSP27 expression (Hettinga et al, 1996). HSP27 overexpression is generally thought to protect against apoptosis triggered by a variety of stimuli, including oxidative stress generated by tumor necrosis factor (TNF) (Mehlen et al, 1996a).…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrated that quercetin could enhance susceptibility of the tumor cells to NK cell-mediated lysis through induction of NKG2D ligands in tumor cells. As HSPs are closely associated with apoptotic resistance and make tumor cells resistant to anticancer therapies, 26 to NK cell-mediated lysis. Then it could be determined whether overexpression of HSP70 reverses the effect of quercetin on the susceptibility of SNU-C4 cells to NK-92 cells.…”
Section: Quercetin Enhances the Susceptibility Of Tumor Cells To Nk Cmentioning
confidence: 99%
“…[16][17][18][19] However, many of these treatments such as 5-fluorouracil, cisplatin, valporic acid, tricostatin A, bortezomib, ionizing radiation, and heat shock of tumor cells, have also been shown to induce heat-shock proteins (HSPs), 20-25 which protect tumor cells from stress conditions and apoptosis. 26,27 As it has been known that the induced HSPs are associated with the resistance of tumor cells to anticancer therapies, [28][29][30] it could be suggested that enhancing the cytotoxicity of NK cells through the induction of NK cells-activating ligands would be limited by the chaperone effects of the HSPs that were simultaneously induced in the tumor cells. An earlier report showed that down-regulation of HSPs in tumor cells could increase the susceptibility to NK cell-mediated cytotoxicity, when tumor cells were treated with ATO, an inducer of NKG2D ligands.…”
mentioning
confidence: 99%